Analisis Isi Komentar Netizen pada Akun TikTok @hiracloud dalam Respons terhadap Konten Motivasi Menulis Skripsi. - Geri Hasbullah; Syahril Furqany; Fitri Meliya Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses a content analysis of netizen comments on the TikTok account @hiracloud in response to content related to motivation for writing a thesis. The research focuses on the reactions of netizens when viewing TikTok content by @hiracloud documenting the thesis-writing process. This study employs a content analysis method with a qualitative descriptive approach. The results show that netizen responses vary widely. Some comments offer emotional support, others share personal experiences, and some express that the content serves as an external source of motivation for writing their thesis. This phenomenon is particularly interesting because the content was not initially intended to motivate students; it was simply a personal documentation of the thesis-writing journey. Nevertheless, it unexpectedly triggered motivational responses from viewers. These findings demonstrate that netizens are indeed inspired to write their own theses after engaging with the content. Therefore, this study is considered significant because it shows how content originally created for personal purposes can evolve into a motivational force for others. It is hoped that similar content will continue to emerge, fostering responses that can further encourage students in their academic writing journey. Additionally, this research is expected to serve as a valuable reference for future studies in related fields.